In vitro biomechanical analysis of the desmotomy of the suspensory navicular ligaments of the equine - Gaona-Urueña, Leonardo (2018)
The objective of this study was to design a biomechanical model of the equine digit and its use in the in vitro analysis of the desmotomy of the suspensory ligaments of the navicular. Ten orthopedically healthy anterior digits of Creole horses were collected and adapted to a laboratory for biomechanical procedures to determine the tension of the superficial and deep digital flexor tendons (TTFDS and TTFDP) and the biomechanical changes of the navicular bone. In total, 86 data were obtained by digit before the surgical procedure and 86 data after the surgical procedure. The force on the navicular bone, the force on the navicular bone between the digits and the force on the navicular bone between surgical times (TQXs) was determined by each digit. Little variability and none significant difference between the experimental repetitions of each digit was observed, as well as statistical similarity of the TQXs of most of the digits; however, significant differences were found when comparing the three-digit TQXs. The inverse dynamic model allowed establishing the tension of the digital flexor tendons and the force on the navicular bone before and after the desmotomy of the suspensory ligaments of the navicular, and none significant force changes were observed.